2019
DOI: 10.12688/f1000research.18506.5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phylogenetic analysis of oral Veillonella species isolated from the saliva of Japanese children

Abstract: Background: As the most frequent infectious disease among children worldwide, dental caries have a strong relationship with oral hygiene status, specifically in the development of infection. However, the study regarding the identification and distribution of oral Veillonella are limited. The oral Veillonella community may affected by the differences in geographical location, age, diet, lifestyle, socio-economic status and oral hygiene status. Here, we studied the oral hygiene status by examining the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
3
9
1
Order By: Relevance
“…In the present study, V. rogosae was predominant and was detected in the samples of all subjects, followed by V. tobetsuensis, V. atypica, and V. dispar. Beighton et al [26], Mashima et al [27], and Djais et al [28] also reported that V. rogosae, V. atypica, and V. dispar were the predominant Veillonella species in the human oral cavity, which is consistent with the present results. However, previous studies using VA reported that V. tobetsuensis was rarely detected in the human oral cavity [27] [28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, V. rogosae was predominant and was detected in the samples of all subjects, followed by V. tobetsuensis, V. atypica, and V. dispar. Beighton et al [26], Mashima et al [27], and Djais et al [28] also reported that V. rogosae, V. atypica, and V. dispar were the predominant Veillonella species in the human oral cavity, which is consistent with the present results. However, previous studies using VA reported that V. tobetsuensis was rarely detected in the human oral cavity [27] [28].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies [5] [6] [26] [27] [28] investigated the prevalence of oral Veillonella species using VA. In the present study using OVSM, oral Veillonella species were detected in all samples from healthy and halitosis subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we observed several individual HMO intakes supported the growth of infant oral bacteria such as Veillonella spp., S. mitis and S . salivarius, which are common oral cavity inhabitants [ 98 , 99 , 100 ]. Furthermore, we observed intakes of 3FL and LNFP II were negatively associated with abundance of S. epidermidis in the infant oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that age, geographic location, diet, and oral health behaviors influence the proportion of oral Veillonella species. One such study ( Djais et al., 2019 ) examined the proportion of oral Veillonella species in the saliva samples of Japanese children 4- to 14-years-old as a measure of their oral health status. Interestingly, the detection of V. rogosae declined with deteriorating oral hygiene status (49.1% in good hygiene vs. 44.4% in moderate hygiene vs. 34.1% in poor oral hygiene).…”
Section: Discussionmentioning
confidence: 99%